Peran Citra Merek Dan Kepercayaan Merek Dalam Mewujudkan Loyalitas Merek Pelanggan KFC - Rismadian, Ivana Azahra; -, Nurhadi (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2021)
Realizing brand loyalty is very important for the company so that the brand continues to be known and firmly entrenched in the minds of consumers. KFC is a well-known brand as well as a pioneer of fast food restaurants in Indonesia. This study aims to determine the effect of Brand Image and Brand Trust on Brand Loyalty. This type of research is quantitative using a data collection method with a questionnaire. The research sample was 385 respondents who made purchases at least twice in a period of one year at KFC in Surabaya who were drawn using purposive sampling technique. Information was collected using a questionnaire. The analysis technique used is Multiple Linear Regression using the SPSS 16 application. The results showed that simultaneously Brand Image and Brand Trust have a significant effect on Brand Loyalty. Partially, Brand Image and Brand Trust have a positive and significant effect on Brand Loyalty.